Dual diborane(4) reactivity: Lewis acid to bind Lewis-basic substrates and electron donor for substrate reduction through stimulated diborane-substrate electron transfer - Haas, Lea; Kistner, Lucas; Roesky, Eva; Mailänder, Luca; Kaifer, Elisabeth; Himmel, Hans-Jörg (Chemistry - a European journal, 2025)
Electron-rich ditriflato- and dibromido-diborane(4) molecules with bridging guanidinate substituents readily eliminate triflate/bromide to give monocationic diboranes displaying a dual reactivity as Lewis acids and electron donors. In this work, we report unprecedented reaction sequences in which pyrazine derivatives are first coordinated to the diborane. These coordination compounds are intensely coloured due to electronic excitations from an electron in the B−B bond to a pyrazine π* orbital. Then, in a second, separate step, electron transfer is triggered by pyrazine methylation, simply by addition of MeOTf, increasing the acceptor strength of the coordinated pyrazine unit. Moreover, our experiments show that electron transfer could be triggered by reaction with an excess of pyrazine. We applied a selection of pyrazine derivatives and studied various mono- and dicationic pyrazine-diborane complexes to evaluate the scope of this novel metallomimetic diborane reactivity.